CORRELATION BETWEEN TOTAL CHOLESTEROL AND HYPERTENSION SEVERITY IN ELDERLY PATIENTS: A STUDY FROM SOUTH DENPASAR, INDONESIA - Arjani, Ida Ayu Made Sri; Made Ratih, Gusti Ayu; Jirna, I Nyoman; Hana Sundari, Cok Dewi widhya; Mastra, Nyoman; Rahmawati, Lukiyani Putri (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background. High cholesterol levels contribute to the formation of atherosclerotic plaques in blood vessels, which can lead to the narrowing of these vessels and increased vascular resistance. Aims This study aims to investigate the relationship between total cholesterol levels and the degree of hypertension among the elderly at UPTD Puskesmas 1 South Denpasar.This study investigates the relationship between total cholesterol levels and hypertension severity among the elderly at UPTD Puskesmas 1 South Denpasar.. Method This research employs an analytical observational design with 43 respondents selected using a consecutive sampling technique. Data were collected through interviews, total cholesterol levels were measured using a Point Of Care Testing (POCT) device, and hypertension was assessed with a sphygmomanomete. Results This research employs an analytical observational design with 43 respondents selected using a consecutive sampling technique. Data were collected through interviews, total cholesterol levels were measured using a Point Of Care Testing (POCT) device, and hypertension was assessed with a sphygmomanometer. Conclusion The study concludes that there is a significant correlation between total cholesterol levels and the degree of hypertension in the elderly